Formation of an Isomeric Mixture of Dienynes Instead of a Diallene - Susanne M. Petrova; Leiv K. Sydnes (Molbank, 2020)
Attempts to convert 1,1,2,2,7,7,8,8-octaethoxyocta-3,5-diyne to a symmetric allene by reduction with lithium aluminum hydride failed. Instead reduction accompanied by isomerization occurred and afforded 1,1,2,7,8,8-hexaethoxyocta-2,6-dien-4-yne as a mixture of three isomers in 63% total isolated yield.